1996
DOI: 10.1080/10473289.1996.10467478
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Airborne Dust from Two Nonferrous Foundries by Physico-chemical Methods and Multivariate Statistical Analyses

Abstract: Airborne particulate matter was sampled at a copper smelter and at an aluminum casting plant. Size, shape, quantity, and microlocalization of chemical species in the particulates were measured using closed cassettes, cascade impactors, scanning electron microscopy, X-ray diffraction, infrared and atomic absorption spectrophotometries, secondary ion mass spectrometry, and photoelectron spectroscopy. Cluster and principal components analyses were used in interpreting results. Aerosol chemistry varies as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…(23) They reported that only 10% of the particles had a d ae less than 1 m and 80% of the aerosol collected had a d ae above 5 m. Michaud et al reported on the results of 23 air samples taken at 3 different sites at a copper smelter. (24) Respirable dust (not copper) fractions ranged between 30-39% of the total particulate matter collected.…”
mentioning
confidence: 99%
“…(23) They reported that only 10% of the particles had a d ae less than 1 m and 80% of the aerosol collected had a d ae above 5 m. Michaud et al reported on the results of 23 air samples taken at 3 different sites at a copper smelter. (24) Respirable dust (not copper) fractions ranged between 30-39% of the total particulate matter collected.…”
mentioning
confidence: 99%
“…Ten to 20 μg m −3 is found at remote sites with no local sources (i.e., even in clean air; Brook, Dunn, & Burnett, 1997). In urban areas 60-220 μg m −3 is typical (Sharma, Arora, & Gupta, 1983;Stelson & Seinfeld, 1981), and in a heavily polluted area, levels may approach 2,000 μg m −3 (Michaud, Brail, Dijon, & Per Ault, 1996;Sharma & Patil, 1992). More than 50 μg m −3 was found (Brand, Gerhard, Below, Georgia, & Heyder, 1991) at heavily polluted sites with high traffic density and/or with local sources in the surroundings; in fact, levels at heavily polluted urban areas may reach 100 μg m −3 on average (Kaneyasu, Ohta, & Murai, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the most commonly used analysis methods, such as infrared spectroscopy or xray diffraction, only provide bulk properties of the sample. While this may be sufficient for homogeneous exposures, for heterogeneous exposures, or when looking for trace contaminants in homogeneous samples, particle-by-particle analysis is often needed for the separate characterization of the individual contributions which make up the total exposure (Cornille et al 1990, De Bock et al 1994, Michaud et al 1996. Moreover, the particles themselves may not be homogeneous-for example, they may have surface coatings (Wallace et al 1990) or they may be aggregates of smaller particles-so that an entire vector of data may be needed for each particle to characterize the exposure fully.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron micrscopy-energy dispersive spectroscopy has often been used in conjunction with AES and other surface analysis techniques for analysis of particulate samples (Childs et al 1996, Grekula et al 1986, Michaud et al 1996. Attempts to use these two techniques together in an integrated fashion have not been common because most instruments do not have both the electron energy analyzer needed for AES along with the x-ray detector needed for SEM-EDS.…”
Section: Introductionmentioning
confidence: 99%